In silico molecular docking and In vitro antimicrobial evaluation of some C5-substituted imidazole analogues - Pavankumar Prabhala; Hemantkumar M. Savanur; Suraj M. Sutar; Krishna N. Naik; Manoj Kumar Mittal; Rajesh G. Kalkhambkar (Elsevier, 2021)
Multi-drug resistant pathogens are becoming hard-to-treat causing severe infections in humans across the globe emphasizing the prevailing need to discover new therapeutic agents. Imidazole is an important five membered heterocyclic unit with extensive biological activities in medicinal chemistry, especially as anti-fungal agent. In this context, we report a series of C5-substituted imidazole drug conjugates (synthesized by Van-Leusen method followed by employing Suzuki, Heck and Sonogashira cross coupling reactions in Ionic Liquids [ILs]) which were assessed for their antimicrobial activities along with in silico molecular docking evaluation. Based on the SAR understanding, molecular docking studies and in vitro evaluations of these molecules, together with the resultant inhibitory efficiencies and binding energies, the compounds 2, 8, 16-20, 24 and 27 were found to be excellent antimicrobial molecular entities. However, among these candidates, especially compounds 8, 16 and 20 found to be the most promising antibacterial drug conjugates showing significant inhibitory potential with MICs ranging from 1 to 16 ​μg/mL against Gram ​+ ​ve strains. In case of antifungal activities, compounds 2, 8, 15-21, 24 and 27 exhibited moderate to excellent inhibitions with MIC values in range of 1-16 ​μg/mL. Perhaps, from the present study compounds 8 and 20 emerge out to be most promising antimicrobial agents with highest binding affinity and maximum inhibition efficiency (1-4 ​μg/mL).